Hybrid Bottom-up/Top-down Energy and Economy Outlooks: A Review of IMACLIM-S Experiments - Ghersi, Frédéric (Frontiers in Environmental Science, 2015)
In this paper we survey the research undertaken at the Centre International de Recherche sur l’Environnement et le Développement (CIRED) on the combination of the IMACLIM-S macroeconomic model with ‘bottom-up’ energy modeling, with a view to associate the strengths and circumvent the limitations of both approaches to energy-economy-environment (E3) prospective modeling. We start by presenting the two methodological avenues of coupling IMACLIM-S with detailed energy systems models pursued at CIRED since the late 1990s’: (1) the calibration of the behavioral functions of IMACLIM-S that represent the producers’ and consumers’ trade-offs between inputs or consumptions, on a large set of bottom-up modeling results; (2) the coupling of IMACLIM-S to some bottom-up model through the iterative exchange of some of each model’s outputs as the other model’s inputs until convergence of the exchanged data, comprising the main macroeconomic drivers and energy systems variables. In the following section, we turn to numerical application and address the prerequisite of harmonizing national accounts, energy balance and energy price data to produce consistent hybrid input-output matrices as a basis of scenario exploration. We highlight how this data treatment step reveals the discrepancies and biases induced by sticking to the conventional modeling usage of uniform pricing of homogeneous goods. IMACLIM-S rather calibrates agent-specific margins, which we introduce and comment upon. In a further section we sum up the results of 4 IMACLIM-S experiments, insisting upon the value-added of hybrid modeling. These varied experiments regard international climate policy burden sharing; the more general numerical consequences of shifting from a biased standard CGE model perspective to the hybrid IMACLIM approach; the macroeconomic consequences of a strong development of electric mobility in the European Union; and the resilience of public debts to energy shocks. In a last section we offer some conclusions and thoughts on a continued research agenda.